The impact of COVID-19 on women’s reproductive system - Dong, Shixiang; Liu, Xia; Wang, Yankui (Frontiers in Medicine, 2024)
Abstract The coronavirus disease 2019 (COVID-19) pandemic has been a major global focus since 2019. However, drug development and vaccination have been unable to stop the rise in the number of COVID-19 infections. As a result, almost everyone has been infected with COVID-19. As the COVID-19 pandemic nears its end, it is important to explore whether contracting COVID-19 has any irreversible effects on the female reproductive system. This article aims to review the effects of COVID-19 on the female ovary and reproductive system and examine whether these effects are permanent. In conclusion, we can state that COVID-19 has not caused any long-lasting effects on the reproductive health of most women, with the exception of a few cases where premature ovarian failure has been observed. These temporary effects, such as menstrual disturbances and temporary fertility loss, tend to diminish and eventually disappear over time.